Case Report: Renal Tubular Acidosis As The Initial Presentation Of Sjogren's Syndrome - John, Dorado; Sebastian, Ramirez; Elias, Galica; Fabian, Garza; Karla, Aguirre; Alejandro, Rico (British Journal of Healthcare and Medical Research, 2024)
Sjögren's syndrome (SSjP) is a chronic multisystem autoimmune disorder characterized by inflammation of the lacrimal and salivary glands, with consequent dryness of the eyes and mouth and occasional glandular enlargement, it occurs in a primary form, not associated with other autoimmune rheumatic diseases. We present the case of a 36-year-old female patient with Sjögren's syndrome whose initial clinical manifestation was extraglandular, with the kidney as the main organ affected in the form of chronic hypokalemia and distal renal tubular acidosis, which led to immunological markers being performed. for Sjögren's syndrome, the diagnosis of this autoimmune exocrinopathy allowed, achieving clinical remission and stabilization of renal function with the use of steroids.